Cordyceps cicadae polysaccharides alleviate hyperglycemia by regulating gut microbiota and its mmetabolites in high-fat diet/streptozocin-induced diabetic mice - Wang, Yanan; Ni, Zaizhong; Li, Jinting; Shao, Ying; Yong, Yidan; Lv, Wendi; Zhang, Simeng; Fu, Tingwei; Chen, Anhui (Frontiers in Nutrition, 2023)
The polysaccharides found in Cordyceps cicadae (C. cicadae) have received increasing academic attention owing to their wide variety of therapeutic activities. This study evaluated the hypoglycemic, antioxidant, and anti-inflammatory effects of polysaccharides from C. cicadae (CH-P). In addition, 16s rDNA sequencing and untargeted metabolomics analysis by liquid chromatography-mass spectrometry (LC-MS) were used to estimate the changes and regulatory relationships between gut microbiota and its metabolites. The fecal microbiota transplantation (FMT) was used to verify the therapeutic effects of microbial remodeling. The results showed that CH-P treatment displayed hypoglycemic, antioxidant, and anti-inflammatory effects and alleviated tissue damage induced by diabetes. The CH-P treatment significantly reduced the Firmicutes/Bacteroidetes ratio and increased the abundance of Bacteroides, Odoribacter, Alloprevotella, Parabacteroides, Mucispirillum, and significantly decreased the abundance of Helicobacter and Lactobacillus compared to the diabetic group. The alterations in the metabolic pathways were mostly related to amino acid biosynthesis and metabolic pathways (particularly those involving tryptophan) according to the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis. Correlation analysis showed that Bacteroides, Odoribacter, Alloprevotella, Parabacteroides, and Mucispirillum were positively correlated with indole and its derivatives, such as 5-hydroxyindole-3-acetic acid. Indole intervention significantly improved hyperglycemic symptoms and insulin sensitivity, and increased the secretion of glucagon-like peptide-1 (GLP-1) in diabetic mice. FMT reduced blood glucose levels, improved glucose tolerance, and increased insulin sensitivity in diabetic mice. However, FMT did not significantly improve GLP-1 levels. This indicates that C. cicadae polysaccharides alleviate hyperglycemia by regulating the production of metabolites other than indole and its derivatives by gut microbiota. This study provides an important reference for the development of novel natural products.